2023
DOI: 10.1126/sciadv.adf0115
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcarnitine shuttling links mitochondrial metabolism to histone acetylation and lipogenesis

Abstract: The metabolite acetyl-CoA is necessary for both lipid synthesis in the cytosol and histone acetylation in the nucleus. The two canonical precursors to acetyl-CoA in the nuclear-cytoplasmic compartment are citrate and acetate, which are processed to acetyl-CoA by ATP-citrate lyase (ACLY) and acyl-CoA synthetase short-chain 2 (ACSS2), respectively. It is unclear whether other substantial routes to nuclear-cytosolic acetyl-CoA exist. To investigate this, we generated cancer cell lines lacking both ACLY and ACSS2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…1K-N and S1 ), these data indicate that energy production and/or ROS are not contributing to the observed effect. Recent publications also demonstrated that acetyl-carnitine is a precursor for nuclear acetyl-CoA that supports histone acetylation (Izzo et al, 2023; Kuna et al, 2023). Using a global mass spectrometry approach, we found that knockdown or inhibition of IDH1 decreased global histone acetylation to a greater extent than histone methylation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1K-N and S1 ), these data indicate that energy production and/or ROS are not contributing to the observed effect. Recent publications also demonstrated that acetyl-carnitine is a precursor for nuclear acetyl-CoA that supports histone acetylation (Izzo et al, 2023; Kuna et al, 2023). Using a global mass spectrometry approach, we found that knockdown or inhibition of IDH1 decreased global histone acetylation to a greater extent than histone methylation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first report of αKG promoting histone acetylation. Histone acetylation is partly controlled by nuclear-cytoplasmic acetyl-CoA pools (Sivanand et al, 2017), and recent work has demonstrated that the endogenous acyl-carrier L-carnitine plays an active role in histone acetylation by shuttling acetyl units in the form of acetylcarnitine from the mitochondria and/or peroxisome and acting as a nuclear acetyl-CoA precursor (Izzo et al, 2023; Kuna et al, 2023). In this study, we have now identified an upstream regulator of the carnitine-histone acetylation axis via the αKGDD TMLHE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Acetyl-CoA produced in the mitochondria (or peroxisome) utilizes the carnitine shuttle via carnitine acetyltransferase (CrAT) to translocate into the nucleocytoplasm. 3,9,10 Once the acetyl-carnitine is in the nucleus, carnitine octanoyl transferase (CrOT) 10 converts it back to acetyl-CoA. Acetyl-CoA metabolism is a potential therapeutic target in diseases including cancer, 1113 metabolic disease, 12,14,15 and neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying the export of these acyl-CoAs from the mitochondrial matrix need to be characterized, but they could rely on the carnitine shuttle system, in particular on the ability of carnitine acetyltransferase (CrAT) to generate a series of acyl-carnitines from short- and medium-chain acyl-CoAs [12]. In support of this model, CrAT-dependent generation of extra-mitochondrial acetyl-CoA [13] was reported.…”
Section: Introductionmentioning
confidence: 99%